Tillage systems affect soil nitrogen availability and interact growth parameters of different faba bean cultivars - AHMED F. M. AL-ENEZY; BASIM A. ZAIDAN; ALI F. ALMEHEMDI; ALAA A. HUSSEIN; MUSTAFA ABED AL-JABBAR SALIH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Al-Enezy AFM, Zaidan BA, Almehemdi AF, Hussein AA, Salih MAA. 2023. Tillage systems affect soil nitrogen availability and interact growth parameters of different faba bean cultivars. Biodiversitas 24: 5558-5564. A field trial was conducted during the winter season of 2021-2022 in one of the agricultural lands of Hamid Shaban village, which belongs to Abu Ghraib District of Baghdad Province (33°17'51.3"N, 44°04'55.0"E). The aim of the experiment was to investigate nitrogen availability in two different tillage systems and the growth characteristics of six broad bean varieties on clay-loamy soils. The field trial was triplicated using the Randomized Complete Block (RCBD) method. The first factor was the six broad bean varieties (Turkish, Dutch, Italian, Spanish, American and local), the second factor was the cultivation system Conservation Tiltage (no-till) and the traditional cultivation with a mouldboard plow. The results showed that the availability of nitrogen in the soil in the traditional tillage system corresponds to the superior to conservative tillage systems. Where this gives an average available nitrogen concentration of 23.3 mg kg-1, an increase of 21 in relation to conservation tillage, which resulted in an average concentration of available nitrogen of 19.1 mg kg-1. In addition, all the growth characteristics of the plants favored the traditional agricultural system. In the variety comparison, the Italian variety was characterized by the highest nitrogen content available in the soil of 26.10 mg kg-1 as well as the highest values ??of plant growth properties among the six varieties.